Income Comparisons and Attitudes towards Foreigners - Walter Hyll; Lutz Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We exploit a natural experiment related to the German re-unification to address the question whether disutility from income comparisons affects attitudes towards foreigners. We find robust evidence that East Germans expose strong negative attitudes towards foreigners, particularly from low-wage countries, if they worry about their economic status compared to better-off West Germans.
Keywords: D31; J61; N34; 330